Competência em informação no contexto da desinformação : um estudo de caso da formação dos discentes no campus de Laranjeiras da Universidade Federal de Sergipe - Pinheiro, Valdiceia de Jesus Cardoso (2021)
The internet and social media foster access and sharing of an exacerbated volume of information; however, its content is not always based on facts, i.e., it is untrue, causing disinformation, which consists of false information produced with or without the intention to harm someone or some group. Therefore, the development of information literacy is relevant to individuals, as it enables the stimulation of citizenship by fostering the autonomy of critical and ethical practices in the information environment for different communities and in multiple contexts. In this sense, the university, as an institution that promotes knowledge through teaching, research and outreach, has in its library a learning center through which it acts on the promotion of knowledge sources and on the recognition of misinformation. In view of this, questions arose about how the Laranjeiras Campus Library (BICAL) could contribute to the (in)formation of students at the Laranjeiras Campus of the Universidade Federal de Sergipe (CAMPUSLAR/UFS). Will the structuring of services of information orientation and use address this demand? The search for genuine information is not a simple task, given that it is necessary to develop competencies to access and use it. This study aims to carry out a formative action to promote the development of information literacy - through the mediation of knowledge that helps in the recognition of misinformation - among the students of CAMPUSLAR/UFS. This research is characterized as an exploratory and descriptive study, with a case study method and a quali-quantitative approach. Data were collected by means of bibliographic research for mapping sources that address: access, mediation, and use of information; misinformation, competence, and information literacy. For data collection, undergraduate and graduate students of CAMPUSLAR/UFS answered a semi-structured online questionnaire. The results indicate that, even though the students understand misinformation as untrue and harmful to society, most of them do not feel able to recognize it. Moreover, they are unaware of the techniques to develop an efficient search in reliable sources of information. This condition contributes to a deficient formation from the informational point of view, as well as to the proliferation and sharing of untrue news or information. Given these findings, the conclusions are that the library fulfills its role as a provider of access to information and that the librarian is the professional endowed with the necessary skills to guide the user‟s education in information literacy. As a product of this study, an animated video containing guidelines for the identification of misinformation was proposed, so as to contribute to the development of critical thinking in the constitution of citizenship.